Engineered variants provide new insight into the structural properties important for activity of the highly dynamic, trimeric protein disulfide isomerase ScsC from Proteus mirabilis. Issue 3 (5th April 2019) - Furlong, Emily J.; Kurth, Fabian; Premkumar, Lakshmanane; Whitten, Andrew E.; Martin, Jennifer L.
Abstract : The structure and function of a bacterial trimeric protein disulfide isomerase was investigated by characterising two variants in which key structural regions were deleted. In one case the effect on structure and function was predictable, while in the other we found unintended consequences for both structure and function. Abstract : Suppressor of copper sensitivity protein C from Proteus mirabilis (PmScsC) is a homotrimeric disulfide isomerase that plays a role in copper tolerance, which is a key virulence trait of this uropathogen. Each protomer of the enzyme has an N‐terminal trimerization stem (59 residues) containing a flexible linker (11 residues) connected to a thioredoxin‐fold‐containing catalytic domain (163 residues). Here, two PmScsC variants, PmScsCΔN and PmScsCΔLinker, are characterized. PmScsCΔN is an N‐terminally truncated form of the protomer with two helices of the trimerization stem removed, generating a protein with dithiol oxidase rather than disulfide isomerase activity. The crystal structure of PmScsCΔN reported here reveals, as expected, a monomer that is structurally similar to the catalytic domain of native PmScsC. The second variant, PmScsCΔLinker, was designed to remove the 11‐amino‐acid linker, and it is shown that it generates a protein that has neither disulfide isomerase nor dithiol oxidase activity. The crystal structure of PmScsCΔLinker reveals a trimeric arrangement, with the catalytic domains packed together very closely. Small‐angle X‐ray scattering analysis found that native PmScsC is predominantly trimeric in solution even at low concentrations, whereas PmScsCΔLinker exists as an equilibrium between monomeric, dimeric and trimeric states, with the monomeric form dominating at low concentrations. These findings increase the understanding of disulfide isomerase activity, showing how (i) oligomerization, (ii) the spacing between and (iii) the dynamic motion of catalytic domains in PmScsC all contribute to its native function.